Ergot alkaloid exposure during gestation alters. I. Maternal characteristics and placental development of pregnant ewes - Britt, Jessica L (J Anim Sci, 2019)
Tall fescue [Lolium arundinaceum (Scheyreb.) Darbysh] is the primary cool season forage grass in the Southeastern United States. Most tall fescue contains an endophytic fungus (Epichloë coenophiala) that produces ergot alkaloids and upon ingestion induces fescue toxicosis. The objective of this study was to assess how exposure to endophyte-infected (E+; 1.77 mg hd(−1) d(−1) ergovaline and ergovalinine) or endophyte-free (E-; 0 mg hd(−1) d(−1) ergovaline and ergovalinine) tall fescue seed fed during 2 stages of gestation (MID, days 35–85/LATE, days 86–133) alters placental development. Thirty-six, fescue naïve Suffolk ewes were randomly assigned to 1 of 4 fescue treatments: E−/E−, E−/E+, E+/E−, or E+/E+. Ewes were individually fed the same amount of E+ or E− seed mixed into total mixed ration during MID and LATE gestation. Terminal surgeries were conducted on day 133 of gestation. Ewes fed E+ fescue seed had elevated (P < 0.001) ergot alkaloid excretion and reduced (P < 0.001) prolactin levels during the periods when fed E+ seed. Ewes switched on day 86 from E− to E+ seed had a 4% reduction (P = 0.005) in DMI during LATE gestation, which translated to a 2% reduction (P = 0.07) in DMI overall. Average daily gain was also reduced (P = 0.049) by 64% for E−/E+ ewes during LATE gestation and tended to be reduced (P = 0.06) by 33% overall. Ewes fed E+ seed during LATE gestation exhibited a 14% and 23% reduction in uterine (P = 0.03) and placentome (P = 0.004) weights, respectively. Caruncle weights were also reduced by 28% (P = 0.003) for E−/E+ ewes compared with E−/E− and E+/E−. Ewes fed E+ seed during both MID and LATE gestation exhibited a 32% reduction in cotyledon (P = 0.01) weights, whereas ewes fed E+ seed only during MID gestation (E+/E−) had improved (P = 0.01) cotyledon weights. The percentage of type A placentomes tended to be greater (P = 0.08) for E+/E+ ewes compared with other treatments. Other placentome types (B, C, or D) did not differ (P > 0.05). Total fetal weight per ewe was reduced (P = 0.01) for ewes fed E+ seed during LATE gestation compared with E−; however, feeding E+ seed during MID gestation did not alter (P = 0.70) total fetal weight per ewe. These results suggest that exposure to ergot alkaloids during LATE (days 86–133) gestation has the greatest impact on placental development by reducing uterine and placentome weights. This, in turn, reduced total fetal weight per ewe by 15% in ewes fed E+ seed during LATE gestation (E−/E+ and E+/E+).